The Collaboration of Mind Mapping Learning With Modeling The Way To Improve Student Learning Outcomes - Siti Fatimah; Sholahudin Al Ayubi; Tri Novita Irawati (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2020)
This study aims to improve student learning outcomes through the collaboration of Mind Mapping learning with Modeling The Way. This type of research is classroom action research (CAR). The subjects of this study were students of class VII MTs. Nurul Islam. The data collection methods used was test, observation, interview and documentation methods. This research was conducted in two cycles, namely cycle I and cycle II. Based on the results of the research conducted, it was obtained data on student learning outcomes before the study was 42.3%, in the first cycle it was 65%, and in the second cycle it was 80%. Based on the results obtained, it can be concluded that the colaboration of  Mind Mapping learning with Modeling The Way can increase student learning outcomes. Keywords: learning outcomes, mind mapping, modelling the way